Istikhdām Kitāb al-Kawākib ad-Durriyyah Bi Waraqah al-`Amal Fī Tadrīs an-Nahw `Alā Asās Ṭarīqah Ḥill al-Musykilāt (Dirāsah Tajrībiyyah Bi Ma`had Putri Muslimat Samalanga) - Nauratul Islami; Mukhlisah Mukhlisah (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2023)
Nahwu is a system for controlling the use of language and is linked to all linguistic skills. And teaching grammar in the third class is using the book al-Kawakib al-Durriyah. When the teacher asked the students to explain the grammatical rules found in other turast books, the students realized the difficulty. And the reasons for the difficulty of applying them in turast books for students memorizing the rules without the exercises. This research aims to identify the process of Nahwu learning by using the book al-Kawakib Al-Durriyah with a student worksheet in Nahwu learning based on the problem-solving method, and to identify their effectiveness, and to identify the students’ response to their use of Putri Muslimat Collage Samalanga. In this research, the researcher adopted experimental research. The community consisted of 316 students, and the researcher chose 55 students as a sample. The researcher observes, interviews, tests, and questionnaires. The researcher found the results that the students' activities got a score of 80.35% which is excellent. As for the teacher's activities, it got a score of 80.35%, which is excellent. As for its use, it indicates that the result of the significance is 0,00 < 0, 05 and it is effective. The value of the questionnaire is 85.97% indicating that excellent.